THE GUIDANCE OF REGULATION GROUP IN IMPROVING DISCIPLINE OF FEMALE STUDENTS AL-MARDLIYYAH ISLAMIC BOARDING SCHOOL PAMEKASAN - Sulaiha Sulaiha; Ach. Baidowi; Ahsan Riadi (INSTITUT AGAMA ISLAM NEGERI METRO, 2021)
Guidance for the regulation group is carried out to discipline the activities of students in Islamic boarding schools. The aims of the study were to describe: (1) the stages of the rule group guidance with Prayitno's theoretical approach, namely the formation stage, the transition stage, the activity stage, and the termination stage, (2) the student discipline, (3) the impact of the regulation group guidance on the student discipline. Qualitative research method with a case study approach. Data collection techniques with interviews to 8 sources, observation, and documentation. Data analysis techniques with condensation, data presentation and conclusions. Technique of data validity by triangulation of techniques and sources. The results showed: (1) Guidance of the regulatory group: the formation stage by planning and deliberation of regulations by the entire board of boarding schools, submitting regulatory approvals to the caretakers of the boarding school. The transitional stage of regulations, with deliberation and delegation of tasks from caregivers to administrators. The stage of regulatory activities, by making a schedule, division of tasks, and controlling the activities of students. Termination stage of the regulation, with the provision of sanctions. (2) Discipline of the students: the sincerity of the students in following and implementing the rules and activities of the Islamic boarding school. (3) Impact: students are increasingly disciplined in following the rules. The conclusion is that the guidance of the Islamic boarding school rules group to discipline students is carried out well. The implications of the research as input for other administrators in implementing regulations in the Islamic boarding school environment.